3D printing of customized key biomaterials genomics for bone regeneration. (March 2022) - Zhang, Boqing; Wang, Wenzhao; Gui, Xingyu; Song, Ping; Lei, Haoyuan; Li, Zhengyong; Zhou, Changchun; Fan, Yujiang; Zhang, Xingdong
Highlights: High throughput chip to screen the biomaterials genomics for regenerative medicine. Distinguishing osteoinduction from osteoconduction in an orthotopic site. Effects of porous structure on the osteoinduction and osteoconduction. Abstract: The rapid development of regenerative medicine has brought new opportunities for disease treatment. However, the clinically adopted approaches are full of technical and translational barriers. At present, the selection and screening efficiency of key material factors in regenerative medicine, such as material category, structure, and performance, is relatively low. The screening process costs a large quantity of materials, manpower, time, and money. The key material factors of bone regeneration include the materials' composition, structure, surface morphology, additives, and so on. They resemble genes in organisms that determine the biological function of cells. The design and screening of biomaterials genomics are crucial for bone tissue engineering scaffolds to achieve osteoinduction and osteoconduction. In this study, we provided a bone regeneration test chip fabricated by digital light projection for high-throughput screening of the biomaterials genomics for bone regeneration. The bone test chip contains various test units that form two channels: one for screening the osteoconduction biofunctions and the other for screening the osteoinduction. It effectively realizes the high-throughput screening of specific biological functions in regenerative medicine. Graphical abstarct: Image, graphical abstract